병아리에서의 日本腦炎 바이러스 증식과 (增殖) 抗體形成 - 박진영; 朴陳映; 백락주; 白樂柱; 성인화; 成仁華; 이호왕; 李鎬汪 (Journal of bacteriology and virology, 1979)
Japanese encephalitis (JE) has been reported not only in the far East but also in Southeast Asia since early 1920. It has been known that wild birds and swine are playing important role in the epidemic of Japanese encephalitis as natural hosts and migratory birds have been suspected to carry the virus from endemic areae of tropic zone to temperate regions in early spring each year. The purposes of the experiments wne to investigate multiplication and antibody formation of JE virus in newborn chicks after inoculation of the virus. The results obtained are summarized as follows. 1. Viremia of JE virus appeared from 2 to S days after inoculation of the virus into chicks subcutaneously. 2. Hemagglutination inhibition antibodies to JE virus were demonstrated on 3rd week after inoculation and then decreased slowly. 3. It has been clemonstrated that subcutaueous inoculation was superior than intrapritoneal route to obtain better yield of virus and antibodies in newly hatched chicks. The above results have indicated that cheap available chicks from hatcheries could be used as a model system to study relationship between JE virus and wild birds.